Effect of microsegregation and bainitic reaction temperature on the microstructure and mechanical properties of a high-carbon and high-silicon cast steel - Basso, Alejandro Daniel (2021)
Bainitic microstructures obtained in high-carbon (HC) and high-silicon (HSi) steels are currently of great interest. Microstructural evolution and the bainitic transformation kinetics of a high-carbon and high-silicon cast steel held at 280, 330, and 380◦ C was analyzed using dilatometry, X-ray diffraction, optical and scanning electron microscopy, and electron backscatter diffraction (EBSD). It is shown that the heterogeneous distribution of silicon (Si), manganese (Mn), and chromium (Cr) associated to microsegregation during casting has a great impact on the final microstructure. The transformation starts in the dendritic zones where there is a lower Mn concentration and then expands to the interdendritic ones. As Mn reduces the carbon activity, the interdendritic areas with a higher Mn concentration are enriched with carbon (C), and thus, these zones contain a greater amount of retained austenite plus martensite, resulting in a heterogeneous microstructure. Higher transformation temperatures promote higher amounts of residual austenite with poor thermal/mechanical stability and the presence of martensite in the final microstructure, which has a detrimental effect on the mechanical properties. Tensile tests revealed that the ultra-fine microstructure developed by the transformation at 280◦ C promotes very high values of both tensile and yield stress (≈1.8 GPa and 1.6 GPa, respectively), but limited ductility (≈2%).